Rowing Against the Tide: The Golden Mussel (Limnoperna fortunei) Leaves DNA Footprints Along Its Invasion Route in South American Rivers - Augusto Luiz Ferreira; Renato Luiz Bot Neto; Vanessa Marín-Ruiz; Leonardo Rosa; Mara Cristina Almeida; Patrícia Dammski Borges de Andrade; Susete Wambier Christo; Roberto Ferreira Artoni (Fishes)
The invasion of the golden mussel has resulted in considerable environmental and socioeconomic alterations, which present a considerable threat to the native biodiversity and sustainability of the region. Understanding the distribution and biological characteristics of this Asian mussel, as well as its interaction with human activities, is of the utmost importance to developing effective strategies for mitigating and preventing its further spread. This study examines the dispersal route and incidence of golden mussels, tracing their movement from initial populations in Argentina to their arrival in the São Francisco River Basin (SFR). The presence of the mussel was confirmed through an integrative assessment that included shell taxonomic analyses and mitochondrial DNA signatures. This assessment identified populations located 7.5 km from the river’s mouth, close to the Atlantic Ocean, in areas such as shrimp farms, artisanal ports, and marinas. The analysis of mitochondrial DNA revealed the presence of South-American-specific and shared ancestral haplotypes in the SFR, Grande River, and Argentina. These findings indicate that intracontinental colonization toward the northeast region of South America originated from Asian populations that entered South America via Argentina. The absence of Asian-specific signatures in the SFR, combined with a geomorphological structure unsuitable for large ports or transoceanic vessels, supports the hypothesis of the intracontinental dispersal of Limnoperna fortunei.